2015
DOI: 10.1007/s00018-015-1878-2
|View full text |Cite
|
Sign up to set email alerts
|

The HERC1 E3 Ubiquitin Ligase is essential for normal development and for neurotransmission at the mouse neuromuscular junction

Abstract: The ubiquitin-proteasome system (UPS) plays a fundamental role in protein degradation in neurons, and there is strong evidence that it fulfills a key role in synaptic transmission. The aim of the present work was to study the implication of one component of the UPS, the HERC1 E3 Ubiquitin Ligase, in motor function and neuromuscular transmission. The tambaleante (tbl) mutant mouse carries a spontaneous mutation in HERC1 E3 Ubiquitin Ligase, provoking an ataxic phenotype that develops in the second month of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 52 publications
5
41
0
Order By: Relevance
“…Early findings in the peripheral nerves of C. elegans suggested that presynaptic formation would be driven by ubiquitination mechanisms (DiAntonio et al 2001). Such a similar demand is likely to be conserved in vertebrate synapses because mice bearing mutations for components of the ubiquitination machinery display severe synaptic defects (Wilson et al 2002;Burgess et al 2004;Saiga et al 2009;Chen et al 2011;Bachiller et al 2015). In line with these studies, we have recently demonstrated that the rate of presynaptic assembly shoots up upon inhibition of the proteasome in developing axons (Pinto et al 2016a).…”
Section: Polyubiquitinated Signals Instruct Assemblysupporting
confidence: 67%
See 1 more Smart Citation
“…Early findings in the peripheral nerves of C. elegans suggested that presynaptic formation would be driven by ubiquitination mechanisms (DiAntonio et al 2001). Such a similar demand is likely to be conserved in vertebrate synapses because mice bearing mutations for components of the ubiquitination machinery display severe synaptic defects (Wilson et al 2002;Burgess et al 2004;Saiga et al 2009;Chen et al 2011;Bachiller et al 2015). In line with these studies, we have recently demonstrated that the rate of presynaptic assembly shoots up upon inhibition of the proteasome in developing axons (Pinto et al 2016a).…”
Section: Polyubiquitinated Signals Instruct Assemblysupporting
confidence: 67%
“…; Bachiller et al . ). In line with these studies, we have recently demonstrated that the rate of presynaptic assembly shoots up upon inhibition of the proteasome in developing axons (Pinto et al .…”
Section: Presynaptic Differentiationmentioning
confidence: 97%
“…However, Purkinje cells seem not to be the exclusive target of the mutation; thus, we have recently reported that 1-month-old tbl/tbl mice—that is, before the beginning of Purkinje cell degeneration—present alterations of their motor performance. This motor impairment was closely related to three main alterations of the neuromuscular junction: (i) the reduction of the motor end-plate size; (ii) the decrease of neuromuscular activity efficiency in vivo ; and (iii) the impairment of the evoked neurotransmitter release (Bachiller et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The detected increase in tbl PC survival, reduced atrophy and increased afferent contacts to tbl PCs, clearly show that physical exercise activated protective mechanisms in mutant mice. However, additional mechanisms such as a reduction of neuromuscolar junction alterations described in tbl mice (Bachiller et al, 2015) could also contribute to the detected functional benefits. A better preservation of cerebellar neurons is in line with the increased deposition of PNN in CN, and it is further strengthened by the incremented expression of BDNF in combination with reduction of deregulated autophagy.…”
Section: Discussionmentioning
confidence: 99%